CAROTENEMIA IN NORMAL SUBJEOTS AND IN SOME CASES OF DEFICIENCY DISEASE IN MEXICO - ROCA, JUAN; LLAMAS, ROBERTO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1948)
Three groups of specific reagents which combine with the SH groups of the sulfhydryl enzymes, namely, 2 oxidizing agents iodoacetamide and 2 mercaptide forming compounds were studied on the isolated frog heart All the compounds caused diminished relaxati
ANS INST BIOL
Keywords: CAROTENEMIA, SUBJEOTS, CASES, DEFICIENCY, DISEASE, MEXICO; CIENCIAS DE LA VIDA; FISIOLOGIA HUMANA; FISIOLOGIA MEDICA